Using Buck Boost Converter In The Solar Cell Of Window Blind - Rozi Ahmad Subkhi Azal; Riny Sulistyowati (Procedia of Engineering and Life Science, 2021)
Solar power has become one of alternative sources for electrical energy which is environmentally friendly. Solar energy-based electricity has been employed widely in the society life. Considering that the placement of solar cell requires wide area, the researcher developed new innovation to locate solar cell vertically. Hence, this research aimed at analyzing the vertical placement of solar cell applied on the window blind so that it could catch the sunlight. The researcher also added Buck Boost Converter system to optimize the output voltage. The result of test demonstrated that output voltage yielded by solar cell on the window blind during close condition gained 13.52V, while in the open window blind condition, it obtained 12.82V. Furthermore, the system of Buck Boost converter functioned well as it could stabilize the voltage for charging the battery on the voltage 13.5V. When the window blind was open, the efficiency got 0.33%, whereas in the close condition, its efficiency earned 0.37%. Overall, the whole solar cell on the window blind could tun on the printer and lamp 20Watts by total load 40Watts for 6 hours.